High-efficiency Al-Cu alloy laser additive manufacturing method under action of flat-topped light beam
By forming the Gaussian beam into a flat top beam, the problem of cracks easily formed in the laser additive manufacturing process of Al-Cu alloy under the Gaussian beam is solved, and the forming efficiency and the density of the parts are significantly improved.
Patent Information
- Application Number
- CN202411664043.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
AI Technical Summary
High-strength Al-Cu alloys are prone to cracks during laser additive manufacturing under Gaussian beams, and low laser process parameters lead to lower production efficiency.
By transforming the laser powder bed melt forming equipment, the Gaussian beam is integrated into a flat-top beam, uniformly distributes the laser energy, stabilizes the turbulence of the laser melt pool, and reduces the thermal gradient, thereby improving the laser forming efficiency.
The forming efficiency of Al-Cu alloy laser additive manufacturing is significantly improved, the manufacturing cycle is reduced, and the formation of three-dimensional solid parts with high density and crack-free is achieved.
Smart Images

Figure CN119566329A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of laser 3D printing process innovation and relates to a high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam. Background Art
[0002] Laser additive manufacturing technology is a high-end digital manufacturing technology based on the discrete-accumulation principle and driven by 3D CAD data to directly manufacture physical parts. Compared with traditional subtractive manufacturing and equal-material manufacturing, laser additive manufacturing technology has the advantages of rapid manufacturing of complex structural products, efficient use of raw materials, highly optimized product structure and adaptability to personalized small-batch production. It is suitable for the increasingly integrated, complex, lightweight and structural and functional integrated manufacturing needs of aerospace equipment, and has been widely used in aviation, national defense, transportation, energy and other fields.
[0003] Al-Cu alloy has become a key material for achieving lightweight structures in the aerospace field because of its excellent properties such as high specific strength, high specific modulus, fatigue resistance and corrosion resistance. However, Al-Cu alloy has a wide solidification temperature range. Under the action of Gaussian beam, the molten pool solidifies quickly and the temperature gradient is large, which is easy to form thermal cracks, leading to early fracture failure of the material. Laser forming under the action of Gaussian beam must reduce laser process parameters such as laser power and scanning speed. Although solidification cracks can be reduced, it is still difficult to change the limitations of uneven energy density distribution of Gaussian beam. At the same time, process parameters such as low laser scanning speed will lead to a significant reduction in forming efficiency. Therefore, Al-Cu alloy laser formed under Gaussian beam has problems such as low forming efficiency, which is difficult to meet actual production needs. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to solve the problem that the high-strength Al-Cu alloy is prone to crack formation during the laser additive manufacturing process under Gaussian beam and the laser process parameters are low, resulting in low production efficiency.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam comprises the following steps: (1) Modify the laser powder bed fusion forming equipment to shape the Gaussian beam into a flat-top beam; (2) Use computer-aided design software to build a 3D solid geometric model of the target part, then use slicing software to slice the model, plan the laser scanning path, and set the laser process parameters to discretize the 3D solid into a series of 2D data; (3) The data obtained in step (2) is imported into a laser powder bed fusion forming device to melt and solidify the spread aluminum alloy powder layer by layer to form a highly dense, crack-free three-dimensional solid part.
[0006] Specifically, in step (1), the laser powder bed fusion forming equipment comprises a laser system (1), a beam expander (2), a triple lens (3) and a reflector (4); at the rear end of the reflector (4), an optical system consisting of a cylindrical lens array (5) and a field lens (6) is arranged to shape a Gaussian beam with concentrated laser energy into a flat-top beam with uniform energy distribution.
[0007] The present invention shapes the Gaussian beam into a flat-top beam, which can eliminate the limitation of excessive energy concentration of the Gaussian beam, evenly distribute the energy, stabilize the turbulence of the laser molten pool, and reduce the thermal gradient, thereby performing laser forming at a higher scanning speed and layer thickness, significantly improving the forming efficiency of Al-Cu laser additive manufacturing and greatly shortening the manufacturing cycle.
[0008] Preferably, the cylindrical lens array (5) comprises two or more cylindrical lens groups arranged in parallel in the transverse direction, the longitudinal pitch of two adjacent cylindrical lens groups is 0.5-0.8 mm, and the distance between two adjacent cylindrical lenses in each cylindrical lens group is 80-120 mm.
[0009] Preferably, the focal length of the field lens (6) is 350-400 mm.
[0010] Preferably, the distance between the cylindrical lens array (5) and the field lens (6) is 450-550 mm.
[0011] Specifically, in step (3), the aluminum alloy powder has a Cu content of 4.77-5.25 wt.%, a Mg content of 0.45-0.75 wt.%, a Mn content of 0.40-0.60 wt.%, a Ag content of 0.24-0.43 wt.%, and the balance is Al.
[0012] Preferably, in step (3), the aluminum alloy powder has a particle size of 12-53 μm.
[0013] Preferably, in step (3), the laser power used in laser powder bed fusion forming is 700-900 W, the laser scanning speed is 700-900 mm / s, the scanning interval is 0.1 mm, and a partitioned island scanning strategy is adopted.
[0014] Specifically, the specific process of step (3) is as follows: (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area line by line according to the pre-designed scanning path, causing the powder layer to melt / solidify rapidly, thereby obtaining the first two-dimensional plane of the part to be formed; (b) The computer control system causes the forming substrate to drop by one powder layer thickness, while the piston of the powder supply cylinder rises by one powder layer thickness, and the powder spreading device re-lays a layer of powder to be processed. The high-energy laser flat-top beam completes the scanning of the second layer of powder according to the slicing information to obtain the second two-dimensional plane of the part to be formed; (c) Repeat step (b), and the powder to be processed is formed layer by layer until the part to be formed is completed.
[0015] Preferably, the laying thickness of each layer of powder is 0.1-0.2 mm. Beneficial Effects
[0016] 1. The present invention adopts a flat-top beam to prepare Al-Cu alloy. The uniform energy density distribution of the flat-top beam can effectively solve the problems of cracking of Al-Cu alloy in Gaussian beam laser forming, greatly improve the forming efficiency of aluminum alloy, and realize high-efficiency laser additive manufacturing of Al-Cu alloy with high formability.
[0017] 2. The present invention does not change the alloy composition, nor does it change the original function and structure of the laser additive manufacturing equipment. It only changes the energy distribution of the laser beam, which is relatively simple to operate, saves production costs, improves production efficiency, and can broaden the engineering application range of Al-Cu alloys.
[0018] 3. Compared with traditional casting, forging, welding, powder metallurgy and machining reduction processing methods, the present invention uses laser additive manufacturing technology to manufacture high-strength aluminum alloy components, which greatly improves the freedom of part design, making it possible to produce high-strength aluminum alloy components with complex structures such as topological optimization and bionic design. The formed components are suitable for aerospace, medical health and other fields with small batches, high forming quality, lightweight, customization, and complexity, broadening the application field of high-strength aluminum alloys.
[0019] 4. The flat-top beam additive manufacturing method used in the present invention can be extended to other metal or alloy materials that are prone to cracking during laser additive manufacturing, thereby broadening the range of available metal materials for laser additive manufacturing and promoting the widespread application of laser additive manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0021] Figure 1It is a schematic diagram of the beam shaping device, wherein 1-laser system, 2-beam expander, 3-triplet lens, 4-reflector, 5-cylindrical lens array, 6-field lens, 7-substrate, and other unchanged parts of the laser powder bed fusion forming equipment are not listed.
[0022] Figure 2 This is the energy distribution diagram of the flat-top beam in Example 1.
[0023] Figure 3 This is the powder melting and molten pool thermodynamic simulation of the laser formed Al-Cu alloy sample under the flat-top beam in Example 1.
[0024] Figure 4 This is a simulation of the molten pool temperature gradient and solidification time of the laser-formed Al-Cu alloy sample under a flat-top beam in Example 1.
[0025] Figure 5 This is an optical image of the laser-formed Al-Cu alloy sample under a flat-top beam in Example 1.
[0026] Figure 6 This is the optical image of the laser-formed Al-Cu alloy sample under the flat-top beam in Example 2.
[0027] Figure 7 This is an optical image of the laser-formed Al-Cu alloy sample under a flat-top beam in Example 3.
[0028] Figure 8 This is the optical image of the Al-Cu alloy sample laser formed under Gaussian beam in comparative example 1.
[0029] Fig. 9 This is the optical image of the laser-formed Al-Cu alloy sample under the flat-top beam in comparative example 2.
[0030] Fig.10 This is the optical image of the Al-Cu alloy sample laser formed under Gaussian beam in comparative example 4. DETAILED DESCRIPTION
[0031] The present invention can be better understood with reference to the following examples.
[0032] Figure 1 The laser powder bed fusion forming equipment modified by the present invention. First, the laser beam emitted by the laser system 1 is formed into a Gaussian beam through a beam expander 2, collimated by a triple lens 3, and then changed its optical path direction by a reflector 4, and then decomposed into many wavelets by a group of cylindrical lens arrays 5, and then focused and overlapped by a field lens 6 to form a flat-top beam with uniform energy distribution on a substrate 7.
[0033] The cylindrical lens array 5 includes two cylindrical lens groups arranged in parallel in the horizontal direction, and the longitudinal pitch between two adjacent cylindrical lens groups is 0.5 mm; the distance between two adjacent cylindrical lenses in each cylindrical lens group is 100 mm. The focal length of the field lens 6 is 350 mm. The distance between the cylindrical lens array 5 and the field lens 6 is 400 mm. In the following examples and comparative examples, the Al-Cu alloy powder has a Cu content of 4.77-5.25 wt.%, a Mg content of 0.45-0.75 wt.%, a Mn content of 0.40-0.60 wt.%, an Ag content of 0.24-0.43 wt.%, and the balance is Al; the Al-Cu alloy powder has a particle size of 12-53 μm; The laser powder bed fusion equipment used is equipped with a multi-mode infrared laser, a laser forming chamber, an automatic powder spreading system, a protective atmosphere device, a computer control circuit system, and a cooling circulation system. Before forming, the sandblasted aluminum alloy substrate is fixed on the workbench of the laser powder bed fusion forming equipment and leveled, and the forming chamber is evacuated and then inert gas is introduced.
[0034] The laser powder bed fusion forming process is as follows: (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area line by line according to the pre-designed scanning path, causing the powder layer to melt / solidify rapidly, thereby obtaining the first two-dimensional plane of the part to be formed; (b) The computer control system causes the forming substrate to drop by one powder layer thickness, while the powder supply cylinder piston rises by one powder layer thickness, and the powder spreading device re-lays a layer of powder to be processed. The high-energy laser beam completes the second layer of powder scanning according to the slicing information to obtain the second two-dimensional plane of the part to be formed; (c) Repeat step (b), and the powder to be processed is formed layer by layer until the part to be formed is completed.
[0035] The above parameters are the optimal parameters. The process parameters can be reasonably selected and appropriately adjusted according to the Al-Cu structure and performance characteristics of different components. Example 1
[0036] (1) By Figure 1 The method shown in the figure integrates simple optical elements to make preliminary improvements to the forming equipment. The Gaussian beam output by the laser passes through a uniform beam system consisting of two cylindrical lens arrays and a subsequent field lens. After the beam is decomposed by the lens array, it is refocused by the field lens and overlapped to form a flat-top beam with uniform energy distribution, as shown in the figure. Figure 2 shown.
[0037] (2) Use computer-aided design software to build a three-dimensional solid geometric model of the target part, then use Materialise Magics software to slice the model, and set the laser scanning path and laser process parameters. The laser process parameters are set as follows: laser power of 800 W, laser scanning speed of 800 mm / s, layer thickness of 0.15 mm, scanning spacing of 0.1 mm, and a partitioned island scanning strategy.
[0038] (3) After the forming is completed, the parts and the substrate are separated by wire cutting to obtain the Al-Cu alloy block sample formed by laser under the flat-top beam.
[0039] Based on the finite volume method, a mesoscopic model of heat and mass transfer, melting and solidification of the melt in the laser molten pool was established. The computational fluid dynamics software Fluent was used to simulate the powder melting process and the change law of the molten pool temperature gradient and cooling rate during the flat-top beam forming of Al-Cu alloy samples. The simulation results are as follows: Figure 3-Figure 4 As shown in the simulation results, under the action of the flat-top beam, the Al-Cu alloy powder can be fully melted and spread, and the temperature distribution of the molten pool is relatively uniform. Compared with the temperature gradient under the Gaussian beam, it is smaller, which reduces stress concentration; the turbulence inside the molten pool is stable, so that the liquid phase has enough time to fill the solidification shrinkage gap and inhibit the formation of solidification cracks.
[0040] According to the standard metallographic sample preparation method, the laser-formed Al-Cu alloy block sample under the flat-top beam was polished and polished. The optical microscope picture is as follows Figure 5 As shown in the figure, no solidification cracks were observed in the laser-formed Al-Cu sample, only a small amount of micropores existed, the laser formability was high, and the forming density reached 99.8%. The forming efficiency of Example 1 was calculated according to the laser forming process parameters. Compared with the crack-free Al-Cu alloy formed at a lower scanning speed of Gaussian beam (<100 mm / s), the forming efficiency of Al-Cu alloy under flat-top beam was increased by nearly 2.6 times. Example 2
[0041] (1) By Figure 1 As shown, simple optical elements are integrated to make preliminary improvements to the forming equipment. The Gaussian beam output by the laser is passed through a uniform beam system consisting of two cylindrical lens arrays and a subsequent field lens. After being decomposed by the lens array, the beam is refocused by the field lens and overlapped to form a flat-top beam with uniform energy distribution.
[0042] (2) Use computer-aided design software to build a three-dimensional solid geometric model of the target part, then use Materialise Magics software to slice the model, and set the laser scanning path and laser process parameters. The laser process parameters are set as follows: laser power of 700 W, laser scanning speed of 700 mm / s, layer thickness of 0.10 mm, scanning spacing of 0.1 mm, and a partitioned island scanning strategy.
[0043] (3) After the forming is completed, the parts and the substrate are separated by wire cutting to obtain the Al-Cu alloy block sample formed by laser under the flat-top beam.
[0044] According to the standard metallographic sample preparation method, the laser-formed Al-Cu alloy block sample under the flat-top beam was polished and polished. The optical microscope picture is as follows Figure 6 As shown, there are no obvious cracks in the laser-formed Al-Cu sample, there are a small amount of pores, it has high laser formability, and the forming density reaches 99.6%. The forming efficiency of Example 2 was calculated according to the laser forming process parameters, and it was found that compared with the crack-free Al-Cu alloy formed at a lower scanning speed of Gaussian beam (<100 mm / s), the forming efficiency of the laser-formed Al-Cu alloy under the flat-top beam was increased by nearly 2.0 times. Example 3
[0045] (1) By Figure 1 As shown, simple optical elements are integrated to make preliminary improvements to the forming equipment. The Gaussian beam output by the laser is passed through a uniform beam system consisting of two cylindrical lens arrays and a subsequent field lens. After being decomposed by the lens array, the beam is refocused by the field lens and overlapped to form a flat-top beam with uniform energy distribution.
[0046] (2) Use computer-aided design software to build a three-dimensional solid geometric model of the target part, then use Materialise Magics software to slice the model, and set the laser scanning path and laser process parameters. The laser process parameters are set as follows: laser power of 900 W, laser scanning speed of 900 mm / s, layer thickness of 0.2 mm, scanning spacing of 0.1 mm, and a partitioned island scanning strategy.
[0047] (3) After the forming is completed, the parts and the substrate are separated by wire cutting to obtain the Al-Cu alloy block sample formed by laser under the flat-top beam.
[0048] According to the standard metallographic sample preparation method, the laser-formed Al-Cu alloy block sample under the flat-top beam was polished and polished. The optical microscope picture is as follows Figure 7As shown, there are only a few cracks and a small amount of pores in the laser-formed Al-Cu sample, which has high laser formability and a forming density of 99.3%. The forming efficiency of Example 3 was calculated according to the laser forming process parameters. Compared with the crack-free Al-Cu alloy formed at a lower scanning speed of Gaussian beam (<100 mm / s), the forming efficiency of the laser-formed Al-Cu alloy under the flat-top beam was increased by nearly 3.2 times. Comparative Example 1
[0049] The experimental steps of Comparative Example 1 are basically the same as those of Example 1, except that the laser beam is not shaped, and a Gaussian beam is used to perform laser forming on the Al-Cu alloy. Figure 8 This is the optical image of comparative example 1. The optical images of Example 1 and comparative example 1 show that, compared with the flat-top beam, when the unshaped Gaussian beam forms Al-Cu alloy at a higher scanning speed, the laser energy is relatively concentrated, the temperature gradient of the molten pool is large, and thermal stress concentration is easily formed in the formed part, resulting in a large number of solidification cracks, even penetrating multiple layers. Due to the obvious increase in the thickness of the Al-Cu alloy layer and the scanning interval during the laser forming process, unmelted powder and unmelted pores appear in the formed sample, resulting in a significant decrease in the forming quality, and the density is only 93.5%, which is difficult to meet the needs of engineering applications. Comparative Example 2
[0050] The experimental steps of Comparative Example 2 are basically the same as those of Example 1, except that the laser power is adjusted to 1000 W. The flat-top beam laser-formed Al-Cu alloy block sample in this comparative example is polished and polished according to the standard metallographic sample preparation method. The optical microscope image is shown in FIG. Fig. 9 As shown in the figure, many circular pores were observed in the laser-formed Al-Cu sample, and the forming density dropped to 96.2%. This is because the excessively high laser power greatly increased the laser energy input, the molten pool temperature increased, and the low-melting-point Al and Mg elements volatilized in large quantities without time to overflow, forming circular pores in the molten pool. Comparative Example 3
[0051] The experimental steps of Comparative Example 3 are basically the same as those of Example 1, except that the laser scanning speed is adjusted to 1200 mm / s. The flat-top beam-formed Al-Cu alloy block sample in this comparative example is ground and polished according to the standard metallographic sample preparation method. The laser-formed Al-Cu sample has a small amount of cracks, irregular melt paths, relatively poor laser formability, and a forming density of 97.4%. The reason is that although the excessively high scanning speed can further improve the forming efficiency, it shortens the solidification time of the molten pool and increases the solidification rate. As the thermal stress increases, stress concentration occurs, forming a small amount of microcracks. Comparative Example 4
[0052] The experimental steps of Comparative Example 4 are basically the same as those of Example 1, except that all parameters are adjusted. A Gaussian beam is used, the laser power is 200 W, the scanning speed is 100 mm / s, the layer thickness is 0.05 mm, and the scanning interval is 0.05 mm. The Al-Cu alloy block sample formed by Gaussian beam laser in this comparative example is polished according to the standard metallographic sample preparation method. The optical microscope picture is as follows: Fig.10 As shown in the figure, no cracks were observed in the laser-formed Al-Cu alloy, but only a small number of micropores. The forming efficiency of Comparative Example 4 was calculated according to the laser forming process parameters. The scanning speed under Gaussian beam was too low. For a sample with a size of 10 mm, the forming time was about 20 hours, which was significantly reduced compared to the flat-top beam laser forming efficiency.
[0053] The present invention provides a high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam. There are many ways to implement this method, and the above is only a preferred way of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented using existing technologies.
Claims
1. A high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam, characterized in that: The following steps are involved: (1) Modify the laser powder bed fusion forming equipment to shape the Gaussian beam into a flat-top beam; (2) Use computer-aided design software to build a 3D solid geometric model of the target part, then use slicing software to slice the model, plan the laser scanning path, and set the laser process parameters to discretize the 3D solid into a series of 2D data; (3) The data obtained in step (2) is imported into a laser powder bed fusion forming device to melt and solidify the spread aluminum alloy powder layer by layer to form a highly dense, crack-free three-dimensional solid part.
2. The high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam according to claim 1 is characterized in that: In step (1), the laser powder bed fusion forming equipment comprises a laser system (1), a beam expander (2), a triple lens (3) and a reflector (4); an optical system consisting of a cylindrical lens array (5) and a field lens (6) is arranged at the rear end of the reflector (4) to shape a Gaussian beam with concentrated laser energy into a flat-top beam with uniform energy distribution.
3. The high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam according to claim 2 is characterized in that: The cylindrical lens array (5) comprises more than two cylindrical lens groups arranged in parallel in the transverse direction, the longitudinal pitch of two adjacent cylindrical lens groups being 0.5-0.8 mm; and the distance between two adjacent cylindrical lenses in each cylindrical lens group is 80-120 mm.
4. The high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam according to claim 2 is characterized in that: The focal length of the field lens (6) is 350-400 mm.
5. The high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam according to claim 2 is characterized in that: The distance between the cylindrical lens array (5) and the field lens (6) is 450-550 mm.
6. The high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam according to claim 1 is characterized in that: In step (3), the aluminum alloy powder has a Cu content of 4.77-5.25 wt.%, a Mg content of 0.45-0.75 wt.%, a Mn content of 0.40-0.60 wt.%, a Ag content of 0.24-0.43 wt.%, and the balance is Al.
7. The high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam according to claim 1 is characterized in that: In step (3), the aluminum alloy powder has a particle size of 12-53 μm.
8. The high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam according to claim 1 is characterized in that: In step (3), the laser power used in laser powder bed fusion forming is 700~900 W, the laser scanning speed is 700~900 mm / s, the scanning interval is 0.1 mm, and a partitioned island scanning strategy is adopted.
9. The high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam according to claim 1, characterized in that: The specific process of step (3) is as follows: (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area line by line according to the pre-designed scanning path, causing the powder layer to melt / solidify rapidly, thereby obtaining the first two-dimensional plane of the part to be formed; (b) The computer control system causes the forming substrate to drop by one powder layer thickness, while the piston of the powder supply cylinder rises by one powder layer thickness, and the powder spreading device re-lays a layer of powder to be processed. The high-energy laser flat-top beam completes the scanning of the second layer of powder according to the slicing information to obtain the second two-dimensional plane of the part to be formed; (c) Repeat step (b), and the powder to be processed is formed layer by layer until the part to be formed is completed.
10. The high-efficiency Al-Cu alloy laser additive manufacturing method under the action of a flat-top beam according to claim 9, characterized in that: The laying thickness of each layer of powder is 0.1-0.2 mm.